The impact of the implementation of a national policy on dementia on healthcare costs in older patients with dementia in Korea: a quasi-experimental difference-in-difference studyResearch in context - Mingee Choi; Woorim Kim; Jong Youn Moon; Jaeyong Shin (Elsevier, 2024)
Summary: Background: Owing to the aging population, the prevalence of dementia is increasing worldwide and has become an important public health problem. In 2018, Korea implemented the National Dementia Care Policy to strengthen the management of dementia and reduce its related burden on medical expenses. This study investigated the effect this policy on total and out-of-pocket costs in elderly patients with dementia. Methods: Data were from the National Health Insurance System. The study population included 10,549,863 individuals aged 65 years or older, recorded between January 1, 2015, and December 31, 2020. The treatment group comprised of dementia patients and the control group those diagnosed with the five most common diseases found in individuals aged 65 years or above. The difference-in-difference was used to explore changes in total and out-of-pocket healthcare costs per diagnosed case between the treatment and control group before and after the intervention period. Findings: Policy implementation was associated with a significant decrease in patient out-of-pocket cost. In the covariate-controlled model, no statistically significant changes were found for total mean healthcare cost. However, patient out-of-pocket cost decreased by 0.05 per diagnosed case. Interpretation: The National Dementia Care Policy led to a reduction in patient out-of-pocket cost in elderly patients with dementia. National policies need to be monitored to reduce the economic burden of patients with dementia while maintaining the financial sustainability of the healthcare system. Funding: This research was financially supported by the Ministry of Trade, Industry and Energy (MOTIE) and Korea Planning & Evaluation Institute of Industrial Technology (Project No. 20024263).